THE CULTURAL CONSTRUCTION OF BARBIE IN AMERICAN DISCOURSES: NORMAN FAIRCLOUGH’S CRITICAL DISCOURSE ANALYSIS - Nisa, Intan Khoirun; Adi, Ida Rochani (Rubikon : Journal of Transnational American Studies, 2023)
The cultural construction of Barbie in American Discourses explains how Barbie as an American popular product is seen, talked about, and understood by the public. Barbie, a fashion doll that has successfully developed into an American icon, has been a subject of discussion since its first publication in 1959. The fact that it supposedly played the role of a simple children’s toy yet can capture the adults’ interests shows that there is something particular in Barbie that might also be deemed relevant by the adults. Thus, this study aims to break down the structure of Barbie as an American popular product in American discourses using Norman Fairclough’s theory of Critical Discourse Analysis. Using Barbie itself as the data taken from Barbie’s official Instagram account, this study applies qualitative methods. The result shows that in American discourses, Barbie is seen as the face of the American Dream and a reflection of Idealized American women. Through the depiction of Barbie’s appearance, the narration of Barbie’s abundant leisure activities, the description of Barbie’s lavish possessions, and their socialite peers, Barbie has symbolically served as an icon in the American Dream. Additionally, Barbie’s position in reflecting the image of American women is seen as the idealized epitome of beauty and success. However, she is also perceived as an icon who brings mixed messages. Even though she aims to promote female empowerment, her representation is also presumed to be problematic and unrealistic.